2003
DOI: 10.1046/j.1471-4159.2003.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the N‐acetylaspartate biosynthetic enzyme from rat brain

Abstract: Aspartate N-acetyltransferase (Asp-NAT; EC 2.3.1.17) activity was found in highly purified intact mitochondria prepared by Percoll gradient centrifugation as well as in the three subfractions obtained after the sucrose density gradient centrifugation of Percoll purified mitochondria; citrate synthase was used as a marker enzyme for mitochondria. The proportion of recoverable activities of Asp-NAT and citrate synthase were comparable in mitochondrial and synaptosomal fractions but not in the fraction containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
1
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 40 publications
(98 reference statements)
2
82
1
2
Order By: Relevance
“…Hypoxia has been linked with decreased mitochondrial enzymes Gibson et al 2000), and reduced levels of membrane-bound enzymes and other proteins (Bruschi and Lindsay, 1994). Because N-acetylaspartate is synthesized in mitochondria (Madhavrao et al, 2003) and considered to reflect neuronal mitochondrial health, its loss may not be associated entirely with dead neurons but could be present in the surviving (and better hypoxia-adapted) neurons, possibly at lower levels. We conclude that under hypoxic exposure surviving neurons show a considerable degree of metabolic adaptation by enhancing glycolysis and decreasing oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been linked with decreased mitochondrial enzymes Gibson et al 2000), and reduced levels of membrane-bound enzymes and other proteins (Bruschi and Lindsay, 1994). Because N-acetylaspartate is synthesized in mitochondria (Madhavrao et al, 2003) and considered to reflect neuronal mitochondrial health, its loss may not be associated entirely with dead neurons but could be present in the surviving (and better hypoxia-adapted) neurons, possibly at lower levels. We conclude that under hypoxic exposure surviving neurons show a considerable degree of metabolic adaptation by enhancing glycolysis and decreasing oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Asp-NAT has been partially purified from rat brain using combined chromatographic techniques including size-exclusion chromatography, which showed that the active enzyme is a high molecular weight protein (~670 kD) with multiple subunits (Madhavarao et al, 2003). Approximately 95% of Asp-NAT activity was lost when the enzyme preparation was treated with 10 mM CHAPS and subjected to size exclusion chromatography.…”
Section: Naa Synthesismentioning
confidence: 99%
“…The predominant astroglial localization of glutamine synthase permits the metabolism of glutamate to glutamine in astrocytes (Martinez-Hernandez et al, 1977;Norenberg and Martinez-Hernandez, 1979;Schousboe et al, 1997), which can then be excreted to the circulation, or recycled to neurons for conversion back to glutamate (Cooper, 2001). As discussed in Section 2.1., neuronal mitochondria express Asp-NAT, a unique enzyme which synthesizes NAA (Benuck and D'Adamo, Jr., 1968;Goldstein, 1969;Madhavarao et al, 2003;Truckenmiller et al, 1985). It had been proposed in the 1970's that NAA synthesis in neuronal mitochondria might be a mechanism for transporting carbon from the mitochondrial matrix to the cytoplasm (Miller et al, 1996;Patel and Clark, 1979), much as citrate does in other cell types (Clark, 1998).…”
Section: A Model Of Naa Synthesis Linked To Mitochondrial Energetics mentioning
confidence: 99%
“…8,9 It has also been suggested that NAA may serve as a readily available precursor of N-acetyl aspartyl glutamate (NAAG), a molecule with neurotransmitter-like properties. 10 Most recently, however, Madhavarao et al 11 have proposed a model in which the synthesis of NAA is an important component of the 'mini citric acid cycle. ' In this process, the extra demand for ATP in neurons is largely met by the oxidation of glutamate via the aspartate aminotransferase pathway.…”
mentioning
confidence: 99%
“…In this way, NAA is hypothesized to play an integral role in the energetics of neuronal mitochondria ( Figure 2). 11 Consequently, although reductions in NAA concentration were formerly thought to indicate neuronal death, 12 recent research has suggested that decreased levels of NAA are more accurately consistent with impaired mitochondrial energy production. 8,13 For example, although traumatic brain injury (TBI) is associated with immediate reductions in NAA, several studies have reported that these levels appear to recover significantly with time, which could not occur if NAA levels were decreased by cell death alone.…”
mentioning
confidence: 99%